The economic and environmental effects of a green employer of last resort: A sectoral multiplier analysis for the United States - Nikolaos Rodousakis; Giuliano Toshiro Yajima; George Soklis (Levy Economics Institute of Bard College, 2022)
We assess the sectoral impact of the implementation of a "green" employer of last resort (ELR) program in the US, based on an environmental modification of an extended Kurz's (1985) multiplier framework and data from OECD Input-Output tables. We use these multipliers to estimate the impact of an "optimal" ELR, designed to maximize the impact on both output and employment while minimizing both imports and carbon emissions. We then test several alternative policy scenarios based upon different compositions of US government expenditure. We provide evidence that (1) investing in the optimal sectors in terms of output, employment, Co2, and import multipliers does not always deliver optimal results in the aggregate; (2) ecological sustainability for the US economy also fosters import sustainability; (3) a rebounding effect in Co2 emissions may be tamed if the ELR satisfies the abovementioned optimality condition, though this undermines its success in terms of output and employment.
Keywords: B52; C67; D57; J68; Q43; 330; Employer of Last Resort; Structural Change; Energy Transition